An emerging Korean youth culture, Rail-ro: the application of cultural consensus analysis to domestic rail travel experiences. Issue 4 (12th March 2017) - Bae, So Young; Chick, Garry
Abstract : This study deals with an emerging domestic rail travel phenomenon among Korean youth, known as Rail-ro ( Railo ), which has influenced aspects of youth culture and domestic tourism in Korea since 2007. The purpose of this study is to determine whether Railo experiences exist as a coherent culture among Railers based on cultural consensus analysis. The result indicates Railers' strong agreement about Railo experiences, which reinforces the view that a particular rail pass could be instrumental in forming a distinct youth travel subculture. This study demonstrates how travel culture driven by the seasonal rail pass supports domestic tourism and inbound tourism.